Repackaging as a Strategy to Increase Efficiency in Extension Programs - Laura Sanagorski (EDIS)
Repackaging is a way to reuse the research and writing one has done on a particular topic by formatting it in multiple formats for several audiences. It can be used as a strategy to reach a greater variety of audiences with fewer resources. This 3-page fact sheet was written by Laura A. Sanagorski, and published by the UF Department of Agricultural Education and Communication, October 2013. http://edis.ifas.ufl.edu/wc155